2012
DOI: 10.1039/c2nr32492j
|View full text |Cite
|
Sign up to set email alerts
|

Nanometer size effects in nucleation, growth and characterization of templated CdS nanocrystal assemblies

Abstract: We report on the oriented nucleation of CdS nanocrystals on well-defined polydiacetylene Langmuir film templates. Nucleation on the red phase of polydiacetylene resulted in ordered linear arrays of CdS nanocrystals that are aligned with respect to the template. High resolution transmission electron microscopy showed crystalline particles of ~5 to 8 nm size. Selected area electron diffraction micrographs showed spot patterns which are attributed to the well-defined orientations of both polymorphs: the cubic zin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

2
21
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 8 publications
(23 citation statements)
references
References 38 publications
2
21
0
Order By: Relevance
“…This implies that en can make the one-dimensional growth of CdS nanocrystals. 35 With further increasing the ratio of en (15-50%), more en molecules are adsorbed and gradually accumulated on the surfaces of CdS nanocrystals because of the strong coordination interaction between en and Cd 2+ , and the CdS nanocrystals adopt a cubic ZB structure at the initial stage of nucleation, and then transform to the bulk stable WZ structure during the growth process, resulting in the appearance of multi-armed nanostructures. 32 This growth mechanism of the multi-armed nanorods corresponds with the typical model in the literature.…”
Section: Crystalline Phase and Morphologymentioning
confidence: 99%
“…This implies that en can make the one-dimensional growth of CdS nanocrystals. 35 With further increasing the ratio of en (15-50%), more en molecules are adsorbed and gradually accumulated on the surfaces of CdS nanocrystals because of the strong coordination interaction between en and Cd 2+ , and the CdS nanocrystals adopt a cubic ZB structure at the initial stage of nucleation, and then transform to the bulk stable WZ structure during the growth process, resulting in the appearance of multi-armed nanostructures. 32 This growth mechanism of the multi-armed nanorods corresponds with the typical model in the literature.…”
Section: Crystalline Phase and Morphologymentioning
confidence: 99%
“…11 Very recently, nucleation of CdS nanocrystals on the red phase of PDA was found to have a size dependent cubic-to-hexagonal transformation. 12 Perylene tetracarboxylic diimide (PDI) derivatives have been extensively and intensively investigated as advanced molecular materials. 13,14 In particular, because of their great potential application as organic semiconductors in different molecular electronic devices, the fabrication of ordered nanostructures of these functional molecular materials has become an attractive research area in the past decade.…”
Section: Introductionmentioning
confidence: 99%
“…Here, we report on mapping charge distribution in a single PbS–CdS heterostructure, which is a system with potential applications in photovoltaic cells. It has been shown that CdS increases power conversion efficiency and photostability of PbS based solar cells. , Chemical synthesis procedures for the preparation of PbS and CdS , nanocrystals have been established. Previous reports of PbS–CdS heterostructures are core–shell and thin film structures, but the synthesis of heterostructures with rock salt–wurtzite phases resulting in differing geometries than core–shell (rock salt–zinc blende) has not been reported.…”
mentioning
confidence: 99%
“…Our motivation to map charge distribution in single PbS–CdS NMHs was their ensemble optical measurements compared to their separate constituents; CdS particles show an absorption edge at 470 nm (Figure a), which is blue-shifted with respect to bulk CdS (515 nm), indicating quantum confinement in nanoparticles. PbS nanoparticles (Figure a) show a blue-shifted sharp onset absorption at 2250 nm, relative to the bulk PbS (3100 nm) .…”
mentioning
confidence: 99%
See 1 more Smart Citation